The School Principal and Teachers' Roles in Improving Learners' Academic Performance at a Selected School in the Karas Region (Namibia) - Сайма Каукевахуло; Девід Нкенгбеза (Hryhorii Skovoroda University in Pereiaslav, 2023)
Objective. The purpose of the study was to investigate the principal and teachers' roles in improving learner's academic performance at a selected school in the Karas region (Namibia). Materials & Methods. The researcher applied a qualitative approach to obtain the qualitative information and deep understanding of the role of the principal and teachers in improving learner's academic performance at a selected school. The teachers and the director of the Karas region took part in the study. The sample consisted of one principal and fourteen teachers, which gave a total sample size of 15 participants. For the study, the researcher used one of the best schools in the region. A purposive sampling was used to choose the participants. Results. The findings of the research revealed that the principal's and teachers' roles in improving learners' academic performance are supervision and monitoring, discipline and decision making, assessment as well as involvement of the learners in extramural activities. Upon executing those roles, they faced some challenges such as lack of teaching and learning resources, misconducting by teachers and learners, failure to meet the set targets, late coming and overcrowded classrooms. These challenges were overcome through motivation, improvising resources, continuous professional development and team building activities. Conclusions. In this scenario, principals are required to work with other stakeholders. Collaborative teaching and discussion should be improved as it will help teachers to improve on teaching and learning. The school principal and teachers should continue to inspire their learners by talking. Teachers are encouraged to continue to play their role in classroom management, guide learners in their learning activities and let the learners use their study time judiciously. Strategic planning should be developed as it will help the stakeholders to focus on key targets for improvement.